2010
DOI: 10.1051/forest/2009086
|View full text |Cite
|
Sign up to set email alerts
|

Response to canopy opening does not act as a filter to Fagus sylvatica and Acer sp. advance regeneration in a mixed temperate forest

Abstract: Abstract• In mixed-species forest stands, large losses in tree species diversity often occur during the regeneration phase. In a former coppice-with-standards, we investigated whether the limiting stage in the recruitment process of advance regeneration is the immediate seedling response to canopy release. Experimental canopy gaps were opened and the survival and growth of advance seedlings (Fagus sylvatica, Acer pseudoplatanus, Acer campestre, Acer platanoides) growing in the gaps or under closed canopy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 42 publications
4
23
1
1
Order By: Relevance
“…The relative growth rate varied significantly in relation to seedling size and was higher for larger seedlings irrespective of shrub environment. This suggests that seedling social status and size prior to shrub removal may be important factors in post-removal growth (Casquet et al 2010). Shrub removal treatment had no significant effect per se on the relative growth rate except in the case of size 2 seedlings under open canopy, which showed the highest competitive-response ability.…”
Section: Discussionmentioning
confidence: 99%
“…The relative growth rate varied significantly in relation to seedling size and was higher for larger seedlings irrespective of shrub environment. This suggests that seedling social status and size prior to shrub removal may be important factors in post-removal growth (Casquet et al 2010). Shrub removal treatment had no significant effect per se on the relative growth rate except in the case of size 2 seedlings under open canopy, which showed the highest competitive-response ability.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the structural equation analysis detected a more consistent effect of browsing than of light, confi rming Abs et al (2008) who showed that the light requirements of Fagus are very similar to those of Tilia and Ulmus, and that shade tolerance of Acer pseudoplatanus and Acer platanoides even exceeds the shade tolerance of Fagus. If protected from browsing, non-Fagus species would become dominant even under conditions of shade (Striepen 2000, Caquet et al 2009). In our study, Fagus had already become dominant by the third height class, having totally suppressed Acer platanoides.…”
Section: Other Factors Explaining Species Loss In Regenerationmentioning
confidence: 99%
“…L'effetto negativo degli intensi interventi di taglio del ceduo effettuati nelle aree indagate (aree campione A, C, D) ha aumentato lo stress ambientale ed ecologico (in termini di modelli di crescita, processi di rinnovazione, effetti dei raggi solari -per esempio si veda: Caquet et al, 2009;Collet et al, 2001;Topoliantz e Ponge, 2000;Robson et al, 2009) dovuto alla frammentazione della copertura forestale e all'apertura delle chiome.…”
Section: Discussione E Conclusioniunclassified